2017
DOI: 10.3389/fpls.2017.00822
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma-Induced Acidification Is an Early Trigger for Changes in Arabidopsis Root Growth and Determines Fungal Phytostimulation

Abstract: Trichoderma spp. are common rhizosphere inhabitants widely used as biological control agents and their role as plant growth promoting fungi has been established. Although soil pH influences several fungal and plant functional traits such as growth and nutrition, little is known about its influence in rhizospheric or mutualistic interactions. The role of pH in the Trichoderma–Arabidopsis interaction was studied by determining primary root growth and lateral root formation, root meristem status and cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 62 publications
5
45
0
4
Order By: Relevance
“…Nieto-Jacobo et al (2017) attributed such phenotype to impaired auxin signaling, whereas Pelagio-Flores et al 2017proposed that acidification of the medium by Trichoderma leads to the loss of root meristem functionality (after 72-96 h of interaction). Interestingly, they also showed that the beneficial effects provided by T. atroviride took place during the first 60 h. Contrastingly, we inoculated Arabidopsis seedlings at the root tips with the wild type and Dhda-2, and observed the inhibition of primary roots and the emergence of lateral roots and branching, but not the negative effects reported by Pelagio-Flores et al (2017). Additionally, the medium amended with 50% and 25% of free-mycelium culture filtrates of Trichoderma showed an enhanced inhibition of plant growth, whereas 12.5% and 6.25% showed enhanced Figure 9.…”
Section: Discussionmentioning
confidence: 75%
“…Nieto-Jacobo et al (2017) attributed such phenotype to impaired auxin signaling, whereas Pelagio-Flores et al 2017proposed that acidification of the medium by Trichoderma leads to the loss of root meristem functionality (after 72-96 h of interaction). Interestingly, they also showed that the beneficial effects provided by T. atroviride took place during the first 60 h. Contrastingly, we inoculated Arabidopsis seedlings at the root tips with the wild type and Dhda-2, and observed the inhibition of primary roots and the emergence of lateral roots and branching, but not the negative effects reported by Pelagio-Flores et al (2017). Additionally, the medium amended with 50% and 25% of free-mycelium culture filtrates of Trichoderma showed an enhanced inhibition of plant growth, whereas 12.5% and 6.25% showed enhanced Figure 9.…”
Section: Discussionmentioning
confidence: 75%
“…Possibly one of the mechanisms involved in root development is due to acidification of the site with the presence of Trichoderma. This process results in the early development of the roots, which after the first days of development occurs an inhibition of the primary root and consequently the development of secondary roots 37,49 , as a mechanism to escape the acidification of the medium. According to Cornejo, Trichoderma enhances the lateral roots instead of the formation of new roots.…”
Section: Discussionmentioning
confidence: 99%
“…Tandon (2019) demonstrated that by alkalinizing the medium in the phosphorus solubilization process, mycelial production and phosphatase activity by Trichoderma decreased significantly, which contributes to the importance of pH in the phosphorus solubilization process 53 . Combined with another mechanism that can be important in the formation of the root system is the production of metabolites, such as auxins and ethylene, produced by a range of Trichoderma species 49,54 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Trichoderma spp. have a strong colonization ability which, with the growth and extension of the root system, can increase the contact area between root and soil and increase the secretion of extracellular enzymes such as sucrase, urease, phosphatase, and organic acids in the rhizosphere, so as to improve the nutrient cycle and enzyme activity in the soil [6,68,69]. Yedidia [70] showed that under a hydroponic system, T. harzianum T203 could significantly increase the nutrient conversion and absorption of P, Fe, Mn, Zn, Cu, and Na, thus promoting cucumber growth and yield.…”
Section: Discussionmentioning
confidence: 99%